TRANSLINGUAL IDENTITIES OF NES AND NNES ENGLISH TEACHERS: A NARRATIVE STUDY - Yohanes Nugroho Widyanto (Widya Mandala Surabaya Catholic University, 2018)
This article reports the study of narratives of research participants, both native and non-native English speaker (NNES) teachers, explore their experiences of learning and teaching English which they reflected during their encounter in Gorontalo. Using Narrative Inquiry as a methodological device, this research facilitates the participants to write their ethnobiographies which were analyzed in order to depict the landscape of their language identities. The analysis shows participants' diverse language identities paradigms ranging from monolingual, multilingual to translingual tendency. Their perspective can be placed into a continuum where Mary (pseudonym), an American veteran English teacher, was on the tendency of monolingual identities and Julie (pseudonym), an English teacher from Indonesia, was on the other end of holding translingual identities.